Anse Flamengo - (:unkn) unknown (My University, 2011)
The postcard shows Anse Flamengo, Tobago. Anse is a creole expression for 'Bay'.
Colour: Black and white; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Bays--Trinidad and Tobago; Anse Flamengo